China's new labour contract law: No harm to employment? - Yu-Fu Chen; Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
In January 2008, China adopted a new labour contract law. This new law represents the most significant reform to the legislation on employment relations in mainland China in more than a decade. The paper provides a theoretical framework on the inter-linkages between labour market regulation, option value and the choice and timing of employment. All in all, the paper demonstrates that the Labour Contract Law in its own right will have only small impacts upon employment in the fast-growing Chinese economy. Rather, induced increasing unit labour costs represent the real issue and may reduce employment.
URN:NBN:fi:bof-201408071939
Keywords: C61; D81; D92; J23; 330; China; labour contract law; real options; employment